OUTCOMES ANALYSIS OF TRANSURETHRAL RESECTION OF THE PROSTATE (TURP) AND TRANSURETHRAL VAPORIZATION OF THE PROSTATE (TUVP) IN PATIENT WITH BENIGN PROSTATE HYPERPLASIA: SYSTEMATIC REVIEW (Indonesian Journal of Urology, 2023)
Objective: This systematic review aims to compare IPSS score and Uroflowmetry (Qmax) results between Transurethral Resection of The Prostate (monopolar and bipolar TURP) and Transurethral Vaporization of The Prostate (PVP, ThuVARP, Biolitec, TUEVP, BPV). Material & Methods: Articles were obtained through online searches using Medline, Google Scholar, and Cochrane Library using keywords Transurethral Resection of The Prostate (TURP) dan Transurethral Vaporization of The Prostate (TUVP) and IPSS or Qmax. Results: A total of 6 RCTs and 3 Cohort consisted of 1212 BPH patients treated with TURP (B-TURP and B-TURP) or TUVP (TUVP, BPV, Biolitec, ThuVARP, GLVP(PVP)). There is a significant difference result of IPSS score and Qmax at the third month of follow-up after both therapies. Conclusion: The post-operative IPSS score and Qmax results at the third month of follow-up in BPH patients treated with TURP or TUVP presents varied results. TURP has a better post-operative IPSS score compared to Biolitec Laser, but not superior when compared with TUEVP, BPV, ThuVARP, and PVP. Notably, TURP has better post-operative Qmax results than BPV, TUEVP, and ThuVARP, but not when compared with PVP.